Karnataka’s ‘Surya Raitha’ experiment: lessons for PM–KUSUM - Durga, N.; Shah, Tushaar; Verma, Shilp; Manjunatha, A.V (2021)
Solar-powered irrigation has expanded in India at an unprecedented pace—the number of solar irrigation pumps—from less than 4,000 in 2012 to more than 2,50,000 by 2019. It has been argued that besides giving farmers an additional and reliable source of income, grid-connected SIPs also incentivise efficient energy and water use—critical for sustaining groundwater irrigation. The Surya Raitha scheme was the country’s first, state-driven initiative for solarisation of agriculture feeders by replacing subsidy-guzzling, inefficient electric pumps with energy-efficient, net-metered SIPs. An early appraisal of Surya Raitha lauded the scheme as a smart initiative and argued that it could set an example for promoting solar power as a remunerative crop. However, the scheme was eventually executed as a single feeder pilot with some design changes in Nalahalli panchayat from 2015–18. The authors visited the pilot in 2017–18 and 2018–19 to assess if it had delivered the promises of Surya Raitha scheme. The results are a mixed bag and offer important lessons for implementation and scaling out of component C of the Government of India’s Pradhan Mantri Kisan Urja Suraksha evam Utthaan Mahabhiyan policy.